Geisteswissenschaften sebagai Landasan Epistemologi: Konsep Erlebnis dan Verstehen dalam Pemikiran Wilhelm Dilthey - Alim, Ansorul; Saputra, Amri; Usman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This research reconstructs Wilhelm Dilthey's epistemology in distinguishing Geisteswissenschaften from the dominance of positivism, examining its relevance to contemporary Big Data hegemony. The study aims to validate Verstehen as an autonomous scientific method without mimicking natural science causality. Through qualitative philosophical hermeneutics, it analyzes the dialectical relationship between Erlebnis, Ausdruck, and Verstehen. Findings indicate: (1) Human sciences' validity is grounded in temporal-qualitative Erlebnis; (2) Knowledge objectivity is attained through analyzing Ausdruck or